An Unlikely Pair: Berlinde De Bruyckere and J.M. Coetzee - Kusek, Robert; Szymański, Wojciech (Werkwinkel, 2015)
Despite J.M. Coetzee’s ostensible interest in the issues of - largely speaking - visuality, the links between Coetzee’s oeuvre and ‘images’ have not been sufficiently explored either by art or literary critics. The paper offers a detailed discussion of the cooperation between Coetzee and the Belgian artist Berlinde De Bruyckere which has so far resulted in one installation and two art books co-authored by Coetzee and De Bruyckere. Special attention will be paid to the piece “Cripplewood/Kreupelhout” shown in the Belgian Pavilion of the 2013 Venice Biennial and the catalogue published in its wake. Also, a number of questions related to the nature of Coetzee’s contribution to both projects, the role of a curator and his relationship with the artist, as well as the catalogue’s generic affiliation and its position in Coetzee’s body of works are thoroughly addressed.